(untitled) (Research, Society and Development, 2020)
Objective: The objective of this article is to report a clinical case in which botulinum toxin type A was applied to the masseter and temporal muscles in order to control pain in a patient diagnosed with Temporomandibular Dysfunction who did not respond to previous treatments, especially for reduction painful symptoms. Methodology: This article is a case report of a clinical, descriptive and analytical nature, which aims to report in detail and based on science, the treatment of a patient who suffered with severe facial pain caused by temporomandibular disorder (TMD). Results: After a careful diagnosis and taking into account the patient’s clinical history of previous unsuccessful treatments for remission of painful symptoms, the reduction of pain reported by the patient was achieved through the application of botulinum toxin to the masseter and temporal muscles, as well as a reduction in pain. volume of the muscles that were hypertrophied and increased amplitude of mouth opening. Conclusion: The application of botulinum toxin to a patient suffering from muscle TMD has proven to be an effective therapy in reducing and controlling the pain reported by the patient. However, more studies are needed, with a longer follow-up and more treated patients.